Development Of Smart Cube Learning Media To Improve Critical Thinking Skills In Children Aged 4–5 Years - Dewi Badriah; Nita Priyanti; Debie Susanti (Kirana Publisher (KNPub), 2026)
This study aims to develop Smart Cube learning media based on problem-solving activities to improve the critical thinking skills of children aged 4–5 years. The research employed a Research and Development (R&D) approach using the ADDIE model, which consists of the stages of analysis, design, development, implementation, and evaluation. The research subjects included children aged 4–5 years and early childhood teachers. Data were collected through observation, interviews, questionnaires, and documentation. The data were analyzed using descriptive quantitative and qualitative techniques. Product validation was conducted by media experts and material experts to determine the feasibility of the developed learning media. The results of the study indicate that the needs analysis revealed the importance of providing concrete, attractive, and interactive learning media capable of stimulating children's critical thinking activities. The developed Smart Cube met both theoretical and empirical feasibility criteria and was categorized as feasible to highly feasible based on expert validation results. Limited trials showed that the Smart Cube was easy for teachers to use and received positive responses from children during learning activities. Furthermore, the effectiveness test demonstrated that the use of Smart Cube learning media effectively improved the critical thinking skills of children aged 4–5 years. Quantitatively, there was an increase in children's critical thinking abilities after the use of the media. Qualitatively, children showed improvements in activeness, curiosity, simple problem-solving abilities, and confidence in expressing their opinions. Therefore, Smart Cube can serve as an innovative and practical learning medium to support the development of critical thinking skills in early childhood education.